ANALISIS PERENCANAAN BAHAN BAKU DI UD. AA DENGAN MENERAPKAN METODE MATERIAL REQUIREMENT PLANNING (MRP) - Rudi Abdika Saputra; Inna Kholidasari; Susanti Sundari; Lestari Setiawati (Jurnal Logistik Indonesia, 2021)
This study discusses the application of the material requirements planning (MRP) method in the planning of raw materials in a furniture company. The purpose of this research is to know the planning of raw materials for furniture products in UD. AA, determine the most suitable inventory model to be applied to material inventory planning and analyze the role of the MRP system in raw material procurement planning. The forecasting method used is the quantitative method of time series analysis, determining the master production schedule, calculating lot sizing (LFL, EOQ, POQ methods). From determining the Master Production Schedule, it is found that the cabinet production plan for the next three months is 4 units per period or week, and based on the calculation of Material Requirement Planning (MRP) it can be seen what components are needed for the manufacture of cabinets, how many and when each component is required. Therefore it is obtained that the total raw material requirement for wood for the next three months is 11.34 m³.